KAJIAN SIFAT SENSORIS, FISIK DAN KIMIA POUND CAKE SUBSTITUSI TEPUNG LABU KUNING (Cucurbita moschata) TERMODIFIKASI ASAM ASETAT - Mayasari, Anastasia; Ishartani, Dwi; Siswanti, Siswanti (Universitas Sebelas Maret (UNS), 2017)
This research aimed to find out sensory, physical and chemical characteristics of pound cake substituted by acetic acid modified pumpkin flour. In this research, sensory characteristics of pumpkin studied included color, taste, texture and overall parameters. Physical characteristics included water level, β-carotene level, and coarse fiber level. The result of research showed that pound cake substituted by acetic acid modified pumpkin flour affected the sensory (color, taste, texture and overall) characteristics. Pound cake with acetic acid modified pumpkin flour substitution of 20% was preferred to the one with other substitution. The use of acetic acid modified pumpkin flour improved yellow color intensity, hardness (Fmax) but lowered expandability of pound cake, increased water level, β-carotene level and coarse fiber level of pound cake.